Newspapers in the time of Sheikh Mahmud The two newspapers Bang Kurdistan (1922) and Roj Kurdistan (1922-1923) as examples: It is a historical study (Raparin Journal of Humanities (RJH), 2024)
During the second reign of Sheikh Mahmud in Sulaimani between 1922-1923, the newspapers Bang Kurdistan and Roj Kurdistan were published. These two newspapers are considered as a second official media of Sheikh Mahmud's government in Sulaimani, although Roj Bang Kurdistan was initially the official media of the Kurdistan Community of Mustafa Pasha Yamulki. But, from the tenth issue, the newspaper became the official media for Sheikh Mahmud's government, thus, we thought to do historical research on these two newspapers to discuss the articles of both newspapers. This study consists of three themes. The first theme explains the political situation in which these two newspapers were published. In the second theme, the two newspapers Bang Haq and Omed Istiqlal are briefly discussed, but the third theme is devoted to the two newspapers Bang Kurdistan and Roj Kurdistan.